Vibration analysis of a specially orthotropic composite laminate with rectangular cutout using independent coordinate coupling method. (15th August 2016) - Huang, Bin; Wang, Ji; Du, Jianke; Ma, Tingfeng; Guo, Yan; Qian, Zhenghua
Abstract: In this paper, the independent coordinate coupling method is further developed and applied for solving the free vibration of a specially orthotropic composite laminate with rectangular cutout. The total energies of the laminate with cutout are calculated by subtracting the energies of the cutout domain from the energies of the laminate domain, where the energies of laminate domain and cutout domain are calculated independently. The mode shape functions of beams with various boundary conditions are considered in each direction as admissible functions. Two coordinate systems are coupled by imposing the displacement matching condition at the cutout domain. So it is very convenient to construct and calculate the mass and stiffness matrices. The effects of modulus ratio, aspect ratio and boundary conditions on the natural frequencies are investigated. The numerical results demonstrate that the proposed methodology can be used as an efficient tool to solve the free vibration problems of specially orthotropic composite laminates with rectangular cutout.